DonnellyOverflow
DonnellyOverflow

Reputation: 4195

Boolean Logic disjunction normal form and Simplified DNF

So I've taken the expression

(¬P∧¬Q∧R∧S)V(¬P∧¬Q∧R∧S)V(¬P∧¬Q∧R∧S)

all the way down to

(P¬∧Q∧R∧¬S)V(R∧S∧¬P)

This is right when I input it into MATLAB unless 2 cancel each other out. What is the simplest way to make this happen. I'm so confused.

Upvotes: 0

Views: 847

Answers (1)

Aditya Vikas Devarapalli
Aditya Vikas Devarapalli

Reputation: 3473

I feel this :

(¬P∧¬Q∧R∧S)V(¬P∧¬Q∧R∧S)V(¬P∧¬Q∧R∧S)

when simplified becomes this :

(¬P∧¬Q∧R∧S)

but not this :

(P¬∧Q∧R∧¬S)V(R∧S∧¬P)

Upvotes: 1

Related Questions